The construction of national identities - Milena Almagro; David Andrés-Cerezo (Theoretical Economics, 2020)
This paper explores the dynamics of nation-building policies and the conditions under which a state can promote a shared national identity on its territory. A forward-looking central government that internalizes identity dynamics shapes them by choosing the level of state centralization. Homogenization attempts are constrained by political unrest, electoral competition and the intergenerational transmission of identities within the family. We find nation-building efforts are generally characterized by fast interventions. We show that a zero-sum conflict over resources pushes long-run dynamics toward homogeneous steady states and extreme levels of (de)centralization. We also find the ability to foster a common identity is highly dependent on initial conditions, and that country-specific historical factors can have a lasting impact on the long-run distribution of identities.
Keywords: B52; D71; D72; D74; H41; H77; P48; Z10; Z13; 330; Cultural evolution; nation-building; national identity; cultural leader; optimal control; political economy; decentralization